Pengembangan Aplikasi Laporkes Sebagai Media Komunikasi Antara Masyarakat Biasa, Fasilitas Kesehatan, Puskesmas, dan Dinas Kesehatan - Amrizal Muchtar; Mardiyyah Hasnawi; Dzul Ikram; Nur Alam Paku Bumi; Arif Rahman; Nur Alifah Salsabila Yani; Husnul Khatimah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Community Health Center (Puskesmas) is the primary healthcare facility in a city. In its daily operations, Puskesmas must frequently interact with the community, healthcare facilities, and local health departments. Currently, at Puskesmas Tamangapa, there is no information system application that effectively mediates communication among them. Therefore, as community-engaged educators, we endeavored to develop a web-based application to address this issue. The method employed in this community engagement project involves creating an application using PHP and Bootstrap programming and promoting the application's usage at Puskesmas Tamangapa. The outcome is an application named 'Laporkes,' accessible at www.laporkes.com. Our conclusion is that this application is quite effective and well-received by all participants in the awareness campaign, with an anticipated launch in the near future.